Perspectives on Lived Religion and Lived Theology - Martina Björkander; Clementine Nishimwe; Sofia Sjö (Approaching Religion)
This thematic issue brings together current research focused on lived religion and/or lived theology. Several of the articles have been developed from papers presented at the national Research Conference in Theology and Religion held in Turku/Åbo in May 2024. The articles explore diverse possibilities of lived perspectives in current research, build on previous literature and critically challenge some of their assumptions. They highlight both the necessity of this perspective and the need for continued theoretical and methodological development.